Efficacy and safety of atezolizumab plus bevacizumab combined with hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma - Xin, Yujing; Cao, Fei; Yang, Hongcai; Zhang, Xinyuan; Chen, Yi; Cao, Xiaojing; Zhou, Xiang; Li, Xiao; Zhou, Jinxue (Frontiers in Immunology, 2022)
Background: Atezolizumab plus bevacizumab has been proved to have promising antitumor activity and tolerable safety in patients with unresectable hepatocellular carcinoma (HCC). Hepatic arterial infusion chemotherapy (HAIC) also demonstrated high response rates and favorable survival for patients with advanced HCC. This study aimed to explore the preliminary clinical efficacy and safety of Atezolizumab plus bevacizumab combined with HAIC for patients with treatment-naive advanced HCC. Methods: Between October 2020 and September 2021, patients with advanced HCC who initially received Atezolizumab plus bevacizumab combined with HAIC of oxaliplatin, fluorouracil, and leucovorin (FOLFOX) from three hospitals in China were reviewed for eligibility. The efficacy was evaluated by tumor response rate and survival, and the safety was evaluated by the frequency of key adverse events (AEs). Results: In total, 52 eligible patients with advanced HCC who received triple therapy were included in this study. The objective response rate (ORR) based on mRECIST and RECIST1.1 criteria were 67.3% and 44.2%, respectively. The median progression-free survival (PFS) of patients was 10.6 months(95%CI, 8.37-13.8), and the overall survival (OS) was not reached. Extrahepatic metastasis was an independent risk factor associated with PFS. All AEs were controlled and no treatment-related deaths occurred. Conclusion: Atezolizumab plus bevacizumab combined with HAIC-FOLFOX had a significant therapeutic effect and manageable adverse events in patients with advanced HCC, which may be a potential treatment option for advanced HCC.